2018
DOI: 10.1016/j.cca.2018.08.026
|View full text |Cite
|
Sign up to set email alerts
|

The association between neutrophil-to-lymphocyte ratio and post-stroke depression

Abstract: Increased NLRs at admission are found to be correlated with PSD and may add prognostic information for the early discovery of PSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 44 publications
1
49
0
Order By: Relevance
“…12,13 Previous studies have been conducted to examine the relationship between NLR and depression after ischemic stroke. 14 However, the association of NLR and depression after ICH has not been clarified. Thus, this study aimed to investigate the predictive value of NLR in depression at 3 months after ICH.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Previous studies have been conducted to examine the relationship between NLR and depression after ischemic stroke. 14 However, the association of NLR and depression after ICH has not been clarified. Thus, this study aimed to investigate the predictive value of NLR in depression at 3 months after ICH.…”
Section: Introductionmentioning
confidence: 99%
“…Microglial cells are thought to be the prime players of the CNS in its own immune and inflammatory responses while pro-apoptotic pathways are activated as a result of the inflammation [46]. While these processes are usually localized to the CNS, a systemic immune response is also manifested as evidenced by peripheral inflammatory biomarkers such as the neutrophil to lymphocyte ratio [47][48][49][50][51]. Using various depression scales such as HAM-D and Quick Inventory for Depression Symptomatology (QIDS), it has been demonstrated that a high NLR ratio on admission predicted PSD after one month [50,52].…”
Section: Ischaemic Cascade and Inflammationmentioning
confidence: 99%
“…27 And there are already many studies using 1 month as evaluation point for PSD. [28][29][30] A score of 0 to 7 is considered to be normal, while a score of ≥7 is indicative of depression. Patients with a HAMD score of ≥7 were evaluated using the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) for the diagnosis of post-stroke depression by a neurologist/psychiatrist who was blind to the laboratory results of stroke patients.…”
Section: Assessmentmentioning
confidence: 99%